Growth modulation and remodeling by means of posterior tethering technique for correction of early-onset scoliosis with thoracolumbar kyphosis - Ahmad, Alaaeldin A.; Aker, Loai; Hanbali, Yahia; Sbaih, Aesha; Nazzal, Zaher (European spine journal, 2017)
Purpose The aim of this study is to evaluate the role of the non-fusion instrumented procedure with compression adjunct to lengthening by distraction in facilitating spinal modulation of the wedged peak vertebra, in patients with congenital thoracolumbar kyphosis/kyphoscoliosis according to the Hueter–Volkmann law. The authors seek to address the progressive modulation of the most wedged vertebra by analyzing the subjects’ pre-operative and latest follow-up sagittal radiograph. Methods Ongoing data collection of 14 peak wedged vertebra modulation during surgical management of 13 patients with Type I congenital thoracolumbar kyphosis (5 patients) or kyphoscoliosis (8 patients). Age at initial surgery averaged 58.6 months, with mean follow-up of 55.6 months (24–78). All were done with hybrid rib construct with clawing fashion through a single posterior approach with at least 4 lengthenings. Results Two vertebral bodies were selected, the peaked deformed vertebrae within the instrumentation compression level (WICL) and the vertebrae nearest but outside the instrumentation compression process (OICL). Anterior vertebral body height (AVBH) and posterior vertebral body height (PVBH) were measured in both vertebral bodies. Regarding measured vertebrae (WICL), average preoperative AVBH/PVBH ratio significantly increased from 0.54 to 0.77 in the final follow-up. Regarding measured vertebrae (OICL), the average preoperative AVBH/PVBH ratio increased from 0.76 to 0.79 in the final follow-up. Modulation can be confirmed in the most deformed vertebrae (WICL) as the difference between the change in AVBH/PVBH ratio between vertebrae (OICL) and (WICL) was statistically significant ( P < 0.001). Conclusions Through the compression model adjunct to lengthening through distraction implemented in the surgical management of early-onset scoliosis, wedging improves through vertebral modulation (WICL) in comparison with the (OICL). This calls for further studies on the impact of surgical correction of EOS on modulation of the vertebrae.